Emergence of Microglia Bearing Senescence Markers During Paralysis Progression in a Rat Model of Inherited ALS - Trias, Emiliano; Beilby, Pamela R.; Kovacs, Mariángeles; Ibarburu, Sofía; Varela, Valentina; Barreto-Núñez, Romina; Bradford, Samuel C.; Beckman, Joseph S.; Barbeito, Luis (Frontiers in Aging Neuroscience, 2019)
Age is a recognized risk factor for amyotrophic lateral sclerosis (ALS), a paralytic disease characterized by progressive loss of motor neurons and neuroinflammation. A hallmark of aging is the accumulation of senescent cells. Yet, the pathogenic role of cellular senescence in ALS remains poorly understood. In rats bearing the ALS-linked SOD1G93A mutation, microgliosis contribute to motor neuron death, and its pharmacologic downregulation results in increased survival. Here, we have explored whether gliosis and motor neuron loss were associated with cellular senescence in the spinal cord during paralysis progression. In the lumbar spinal cord of symptomatic SOD1G93A rats, numerous cells displayed nuclear p16INK4a as well as loss of nuclear Lamin B1 expression, two recognized senescence-associated markers. The number of p16INK4a-positive nuclei increased by 4-fold while Lamin B1-negative nuclei increased by 1,2-fold, respect to non-transgenic or asymptomatic transgenic rats. p16INK4a-positive nuclei and Lamin B1-negative nuclei were typically localized in a subset of hypertrophic Iba1-positive microglia, occasionally exhibiting nuclear giant multinucleated cell aggregates and abnormal nuclear morphology. Next, we analyzed senescence markers in cell cultures of microglia obtained from the spinal cord of symptomatic SOD1G93A rats. Although microglia actively proliferated in cultures, a subset of them developed senescence markers after few days in vitro and subsequent passages. Senescent SOD1G93A microglia in culture conditions were characterized by large and flat morphology, senescence-associated beta-Galactosidase (SA-β-Gal) activity as well as positive labeling for p16INK4a, p53, matrix metalloproteinase-1 (MMP-1) and nitrotyrosine, suggesting a senescent-associated secretory phenotype (SASP). Remarkably, in the degenerating lumbar spinal cord other cell types, including ChAT-positive motor neurons and GFAP-expressing astrocytes, also displayed nuclear p16INK4a staining. These results suggest that cellular senescence is closely associated with inflammation and motor neuron loss occurring after paralysis onset in SOD1G93A rats. The emergence of senescent cells could mediate key pathogenic mechanisms in ALS.